Without an equality sign the given expression can't be considered to be a straight line equation
Chat with our AI personalities
If you mean: 2y = -4x-12 then y = -2x-6 and -6 is the y intercept
2y - 4x = -12 Algebraically rearrange to 2y = 4x - 12 Divide both sides by '2' y = 2x - 6 So at the 'y' intercept, x = 0 Substituting x = 0 We have y = 2(0) - 6 Anything multiplied '0' is equal; to '0' Hence y = 0 - 6 y = -6 is the value of the y-intercept.
4x+2y = 6 2y = -4x+6 y = -2x+3 Perpendicular slope is 1/2
It simplifies to: -4x-12
4x + 2y = 6